A Política de Financiamento da Educação Básica no Município de Cascavel - Paraná (2008-2019) - Vendrame, Josiane Maria (2020)
This work aims to analyze, within the scope of educational policies, the financing policy for Brazilian education, considering its legal, budgetary and financial aspects, and specifically the financing policy for education in the Municipality of Cascavel - PR, between 2008 - 2019. Our intention was to understand how Brazilian financing policies are organized, as well as the relationships that permeate the distribution of these resources. In this direction, to understand our object of study, we organized our methodological path as follows: we investigated the aspects relevant to the concept of the State and social policies in Brazil from the State Reform process in the 1990s, considering the context of economic- policies that took place at the end of the 20th century, in order to understand how the neoliberal regime determines social policies, as well as how the State organizes and implements its actions. We have advanced in the analysis of the legal, budgetary and financial aspects of Education in Brazil after 1990, seeking to understand its structure and functioning from the policy of the Funds for Education: Maintenance and Development of Education - MDE, the Fund for Maintenance and Development of Education Basic and Valuation of Education Professionals - FUNDEB and Salário Educação. Regarding the analysis of the financing policy for education in the Municipality of Cascavel - PR, we focus on the legal, budgetary and financial aspects, its structure and operation based on the policy on education funds. We analyze how it is organized and how the resources actually allocated to the municipality are directed. In the analysis of the structure of Basic Education financing in Brazil, with its fund policy, we observed several problems such as losses caused by inflation, tax waiver, tax evasion, fiscal / economic policy, non-application of funds legally linked by different government spheres and the inequality of available resources at both the federal, state and municipal levels. However, with regard to the application of resources in the municipality of Cascavel, we observe that it followed the proposals of national educational policies, especially with regard to the fulfillment of the financing targets provided for in the national documents, justifying the amount of resources actually allocated for the financing of public policy for basic education in the municipality.